Alpha-alumina carrier, preparation method thereof, silver catalyst, method for producing epoxy compound through olefin epoxidation and application
By using components such as organic oily liquids to prepare α-alumina support, the problem of impurities introduction in the preparation of carriers in the prior art is solved, and the effect of optimizing the channel structure and improving the performance of silver catalysts is achieved.
Patent Information
- Application Number
- CN202311085411.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-08-25
AI Technical Summary
In the existing α-alumina support preparation methods, pore-forming agents and lubricants are often required to add pore-forming agents and lubricants, resulting in the introduction of impurities and affecting the performance of silver catalysts.
The α-alumina carrier is prepared by components such as organic oily liquids, aluminum hydroxide, aluminum oxide, silicon-containing compounds, alkaline earth metal compounds and mineralizers, and suitable pore structure and permeability are formed by acid solution treatment.
Without the need to add pore-forming agents and lubricants, an α-alumina support with optimized pore permeability and low torsion is prepared, which improves the performance and economics of the silver catalyst.
Smart Images

Figure BDA0004416365440000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and more specifically, to an alpha-alumina carrier and a preparation method thereof, a silver catalyst, and a method and application of producing epoxy compounds by olefin epoxidation. Background Art
[0002] Alumina, as a commonly used catalyst carrier, has a large specific surface area, good thermal stability, high mechanical strength and good texture, which has attracted widespread attention and in-depth research. It is a widely used and mature catalyst carrier. Alumina has a variety of crystalline phases, among which the most common ones are γ, δ, κ, η, θ, α, etc. Among these phases, the α phase is a stable phase, and the rest are metastable phases. In current industrial applications, the technical means of preparing α-alumina carriers by calcining aluminum hydroxide precursors is relatively common. During the calcination of the precursor, the generated amorphous alumina is transformed into metastable alumina. This process belongs to the non-lattice reforming process. After calcination at a sufficiently high temperature, these metastable aluminas can be transformed into α-alumina. Among the different crystalline forms of alumina, γ-alumina and α-alumina are the most common as catalyst carriers.
[0003] At present, α-alumina carrier is the only effective carrier of silver catalyst used in olefin epoxidation reaction. In the prior art, in addition to the silver component, the silver catalyst usually has one or more other elements co-deposited on the carrier. The other elements act as an auxiliary agent or co-auxiliary agent to improve the catalytic performance of the silver catalyst. The carrier is usually composed of α-alumina with a suitable pore structure. The α-alumina carrier with a suitable pore structure can not only promote the deposition of active components on the carrier, but also improve the catalytic performance of the silver catalyst. This is because the suitable pore structure can provide sufficient space for the olefin epoxidation reaction, so that the reaction heat can be diffused out in time, and on the other hand, it is also conducive to the timely desorption of the target product epoxide. The parameters for measuring the pore structure of the α-alumina carrier are pore volume, pore size, and pore size distribution.
[0004] The materials for preparing the α-alumina carrier of the silver catalyst generally include: alumina and / or aluminum hydroxide, a binder, an additive, a solid pore former, and a lubricant. Alumina and aluminum hydroxide provide aluminum sources, the binder bonds the raw materials of different components together for easy molding, and the additive improves the performance of the carrier. The solid pore former decomposes and leaves during the roasting process, so that the final carrier has a suitable pore distribution. Currently, solid pore formers include carbonaceous materials, powdered plastics, cellulose, wood chips and other plant materials. However, these pore formers usually introduce impurities, which are not conducive to the performance of the silver catalyst. The lubricant reduces friction and facilitates the molding of the carrier. Summary of the invention
[0005] The purpose of the present invention is to break through the conventional α-alumina carrier preparation method and pore structure characterization ideas through extensive and in-depth research in the field of α-alumina carrier and silver catalyst preparation in view of the above-mentioned state of the prior art, and select organic oily liquid, aluminum hydroxide, optional aluminum oxide, optional silicon-containing compound, optional alkaline earth metal compound and optional mineralizer to prepare α-alumina carrier. Organic oily liquid can reduce the friction between material particles and between material and equipment, increase its fluidity, facilitate carrier molding, and extend the service life of mechanical equipment. It is also found that the α-alumina carrier prepared by the present invention not only has a suitable pore structure, but also has microscopic pores with low tortuosity and good permeability, which is conducive to improving the uniformity of active component silver and auxiliary agent on the surface and inside of the carrier, and is also conducive to the reactant molecules in the catalytic reaction to fully diffuse into the inside of the catalyst and the product molecules to desorb in time, thereby improving the catalytic performance of the catalyst.
[0006] A first aspect of the present invention provides an α-alumina carrier, wherein the α-alumina carrier is prepared by a method comprising the following steps:
[0007] (1) uniformly mixing an organic oily liquid, aluminum hydroxide, optional aluminum oxide, optional silicon-containing compound, optional alkaline earth metal compound and optional mineralizer to obtain a solid mixture;
[0008] (2) kneading, shaping, drying and calcining the solid mixture and the acid solution to obtain the α-alumina carrier;
[0009] Wherein, the kinematic viscosity of the organic oily liquid is ≥10mm 2 / s, preferably ≥20mm 2 / s.
[0010] The second aspect of the present invention provides a method for preparing the above-mentioned α-alumina carrier, the preparation method comprising:
[0011] (1) uniformly mixing the organic oily liquid, aluminum hydroxide, optional aluminum oxide, optional silicon-containing compound, optional alkaline earth metal compound and optional mineralizer to obtain the solid mixture;
[0012] (2) The solid mixture and the acid solution are kneaded, molded, dried and calcined to obtain the α-alumina carrier.
[0013] The third aspect of the present invention provides a silver catalyst, which is prepared by a preparation method comprising the following steps: first, the above-mentioned alumina carrier is impregnated with a solution containing an organic amine, a silver-containing compound, an alkali metal additive, an alkaline earth metal additive, an optional rhenium additive and an optional co-additive of the rhenium additive, and then the impregnation solution is leached; and then the carrier obtained by leaching is activated to obtain the silver catalyst.
[0014] The fourth aspect of the present invention provides a method for producing an epoxy compound by epoxidation of an olefin, the method comprising: epoxidation of the olefin in the presence of the above-mentioned silver catalyst to obtain the epoxy compound;
[0015] The olefin is preferably at least one selected from styrene, propylene, ethylene and 1,3-butadiene.
[0016] The fifth aspect of the present invention provides the use of the epoxy compound produced by the above method as a raw material for producing at least one of ethylene glycol, ethylene glycol ether and ethanolamine.
[0017] The technical solution of the present invention has the following beneficial effects:
[0018] (1) The α-alumina carrier provided by the present invention can be prepared by adding an organic oily liquid with a suitable kinematic viscosity during the preparation process without adding other pore-forming agents and lubricants.
[0019] (2) The present invention can optimize the permeability of the pores of the α-alumina carrier and improve the performance of the silver catalyst prepared therefrom by selecting organic oily liquids of different kinematic viscosities.
[0020] (3) The preparation method of the α-alumina carrier of the present invention is simple and does not introduce impurity elements, so it is more economical and environmentally friendly, and meets the requirements of industry development.
[0021] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0022] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein.
[0023] A first aspect of the present invention provides an α-alumina carrier, wherein the α-alumina carrier is prepared by a method comprising the following steps:
[0024] (1) uniformly mixing an organic oily liquid, aluminum hydroxide, optional aluminum oxide, optional silicon-containing compound, optional alkaline earth metal compound and optional mineralizer to obtain a solid mixture;
[0025] (2) kneading, shaping, drying and calcining the solid mixture and the acid solution to obtain the α-alumina carrier;
[0026] Wherein, the kinematic viscosity of the organic oily liquid is ≥10mm 2 / s, preferably ≥20mm 2 / s.
[0027] According to the present invention, preferably, the organic oily liquid comprises alkanes and / or aromatic hydrocarbons, preferably at least one of normal alkanes, cycloalkanes and aromatic hydrocarbons, and further preferably at least one of white oil, paraffin oil, rubber oil and naphtha;
[0028] The white oil is preferably at least one of medical grade white oil, food grade white oil, cosmetic grade white oil and industrial grade white oil.
[0029] According to the present invention, preferably, the aluminum hydroxide comprises aluminum oxide monohydrate and optionally aluminum oxide trihydrate;
[0030] The alumina monohydrate is at least one of boehmite, diaspore and pseudo-alumina monohydrate;
[0031] The alumina trihydrate is at least one of gibbsite, diaspore and diaspore.
[0032] The aluminum hydroxide of the present invention is converted into intermediate transition state aluminum oxide by high temperature calcination, and finally converted into α-aluminum oxide.
[0033] According to the present invention, in addition to aluminum hydroxide providing an aluminum source, the present invention may also use aluminum oxide, preferably, the aluminum oxide includes at least one of γ-alumina, θ-alumina, κ-alumina, η-alumina and α-alumina;
[0034] In order to improve the performance of the α-alumina carrier, the present invention can also optionally add a silicon-containing compound as an auxiliary agent; the silicon-containing compound includes at least one of silicon-containing sol, silicon dioxide, silicic acid, organic silicon and silicate;
[0035] The alkaline earth metal compound is selected from at least one of the oxides, hydroxides, nitrates, acetates, oxalates and sulfates of alkaline earth metals; the alkaline earth metal is at least one of magnesium, calcium, strontium and barium;
[0036] The mineralizer is selected from at least one of ammonium fluoride, magnesium fluoride, aluminum fluoride, lithium fluoride, boric acid, zinc fluoride, ammonium chloride and ammonium nitrate.
[0037] In the present invention, the performance of the α-alumina carrier is improved by adding a mineralizer to change the alumina crystal transformation process.
[0038] According to the present invention, preferably, based on the total weight of the solid mixture, the amount of the organic oily liquid is 1.0-30.0wt%, the amount of the gibbsite is 15.0-99.0wt%, the amount of the gibbsite is 0-80.0wt%, the amount of the alumina is 0-60.0wt%, the amount of the silicon-containing compound is 0-10.0wt%, the amount of the alkaline earth metal compound is 0-5.0wt%, and the amount of the mineralizer is 0-10.0wt%.
[0039] According to the present invention, preferably, the acid solution includes at least one of a citric acid aqueous solution, a nitric acid aqueous solution, a formic acid aqueous solution, an oxalic acid aqueous solution, an acetic acid aqueous solution, a propionic acid aqueous solution and a hydrochloric acid aqueous solution.
[0040] In the present invention, the added acid solution can generate aluminum sol with part of aluminum hydroxide, and bond the components together to form a paste that can be extruded. The amount of the acid solution and the acid content therein are limited to meet the requirement that the mixed raw material can become a paste that can be extruded; preferably, the mass ratio of acid to water in the acid solution is 1:0.2-10.
[0041] In the present invention, preferably, the components in the solid mixture and the acid solution do not need to be mixed in a specific order. For example, the mineralizer in the solid mixture can also be dispersed or dissolved in the acid solution and then added to the solid mixture.
[0042] In order to mix the mixture uniformly, the present invention kneads the mixture. Kneading and mixing can be performed independently or continuously. The present invention has no particular limitation on the timing of adding the acid solution during the kneading process, as long as the acid solution is added during the kneading process and then kneaded to a desired degree.
[0043] In the present invention, preferably, the molding method may include extrusion molding, horizontal molding, tablet molding or roll cutting molding, and the carrier molding shape includes spherical, cylindrical, annular, multi-leaf clover, porous cylindrical, pill, block or other shapes.
[0044] After forming, the carrier is dried. According to the present invention, preferably, the drying temperature is 60-120°C;
[0045] In order to obtain an α-alumina carrier with suitable properties, the present invention bakes the dried shaped product; the baking temperature is 1000-1600° C., and the baking time is 1-70 hours.
[0046] In the present invention, preferably, the roasting device includes a muffle furnace, a tunnel kiln, a microwave roasting device, a roller kiln or a bell kiln.
[0047] In the present invention, aluminum hydroxide and / or aluminum oxide are substantially converted into α-alumina after high-temperature calcination, and the mass content of α-alumina in the α-alumina carrier of the present invention is ≥95%.
[0048] According to the present invention, preferably, the α-alumina carrier has at least one of the following characteristics: porosity ≥45%, preferably ≥60%; tortuosity ≤40, preferably ≤23.
[0049] The second aspect of the present invention provides a method for preparing the above-mentioned α-alumina carrier, the preparation method comprising:
[0050] (1) uniformly mixing the organic oily liquid, aluminum hydroxide, optional aluminum oxide, optional silicon-containing compound, optional alkaline earth metal compound and optional mineralizer to obtain the solid mixture;
[0051] (2) The solid mixture and the acid solution are kneaded, molded, dried and calcined to obtain the α-alumina carrier.
[0052] The third aspect of the present invention provides a silver catalyst, which is prepared by a preparation method comprising the following steps: first, the above-mentioned alumina carrier is impregnated with a solution containing an organic amine, a silver-containing compound, an alkali metal additive, an alkaline earth metal additive, an optional rhenium additive and an optional co-additive of the rhenium additive, and then the impregnation solution is leached; and then the carrier obtained by leaching is activated to obtain the silver catalyst.
[0053] After preparing the α-alumina carrier of the present invention, those skilled in the art can prepare the silver catalyst of the present invention by known means or any conventional means, such as impregnating the α-alumina carrier with a solution containing a sufficient amount of an organic amine, a silver-containing compound, an alkali metal promoter, an alkaline earth metal promoter, an optional rhenium promoter, and an optional co-promoter of the rhenium promoter.
[0054] In the present invention, preferably, the carrier obtained by leaching is activated in a gas atmosphere containing oxygen.
[0055] In the present invention, the organic amine is added to form a silver amine complex with the silver compound. The organic amine includes one or more of pyridine, ethylamine, n-propylamine, n-butylamine, isobutylamine, tert-butylamine, sec-butylamine, 1,2-propylenediamine, 1,3-propylenediamine, ethylenediamine, 1,2-butylenediamine, 1,3-butylenediamine, ethanolamine, propanolamine and butanolamine.
[0056] In the present invention, during the preparation of the silver catalyst, the silver-containing compound includes one or more of silver oxide, silver nitrate and silver oxalate, and the mass of the silver element accounts for 10-40% of the mass of the silver catalyst.
[0057] In the present invention, in the process of preparing the silver catalyst, the alkali metal auxiliary agent includes one or more of nitrates, sulfates and hydroxides of alkali metals, and the alkali metal includes at least one of lithium, sodium, potassium, rubidium and cesium; the content of alkali metals in the silver catalyst is 5 to 2000 ppm based on the total weight of the silver catalyst. The alkali metal auxiliary agent can be applied to the carrier before, at the same time, or after the impregnation of silver, or can be impregnated on the carrier after the impregnated carrier is activated.
[0058] In the present invention, in the process of preparing the silver catalyst, the alkaline earth metal additive includes one or more of acetates, oxalates, sulfates and nitrates of alkaline earth metals, and the alkaline earth metal includes at least one of magnesium, calcium, strontium and barium; based on the total weight of the silver catalyst, the content of the alkaline earth metal in the silver catalyst is 5 to 20,000 ppm.
[0059] In the present invention, in the process of preparing the silver catalyst, the rhenium promoter includes one or more of rhenium oxide, ammonium perrhenate, perrhenic acid and cesium perrhenate; based on the total weight of the silver catalyst, the content of rhenium in the silver catalyst is 0 to 10,000 ppm, preferably 50 to 10,000 ppm. In the present invention, in the process of preparing the silver catalyst, the co-promoter of the rhenium promoter includes one or more of cerium, sulfur, molybdenum, chromium salts or oxygen anions in acid form.
[0060] In the present invention, in the process of preparing the silver catalyst, in order to fully impregnate the α-alumina carrier prepared by the above method with a solution containing a sufficient amount of organic amine, silver compound, alkali metal auxiliary agent, alkaline earth metal auxiliary agent, optional rhenium auxiliary agent and optional co-auxiliary agent of rhenium auxiliary agent, the α-alumina carrier is usually impregnated under the condition of vacuum degree less than 10 mmHg, and the impregnation time is 5 to 60 minutes. After impregnation, the impregnation solution is leached and then activated in air or nitrogen-oxygen mixed gas with an oxygen content of not more than 21% by volume, the activation temperature is 150 to 400° C., and the activation time is 1 to 120 minutes.
[0061] In some embodiments of the present invention, the silver catalyst further comprises other elements deposited on the α-alumina carrier, and the other elements comprise at least one of phosphorus, boron, chromium and titanium.
[0062] In the present invention, in order to prepare the silver catalyst of the present invention, preferably, an aqueous solution of silver nitrate can be first reacted with an aqueous solution of ammonium oxalate or oxalic acid to precipitate a silver oxalate precipitate, which is then filtered and washed with deionized water until no nitrate ions are present. The silver oxalate is then dissolved in an aqueous solution of an organic amine, and an alkali metal auxiliary agent, an alkaline earth metal auxiliary agent, an optional rhenium auxiliary agent and a co-auxiliary agent of the rhenium auxiliary agent are added to form an impregnation solution. The obtained impregnation solution is used to impregnate the α-alumina carrier prepared by the above method, the impregnation solution is leached, and the silver catalyst is finally prepared.
[0063] In order to obtain a silver catalyst with a higher silver content and / or promoter content, the present invention can prepare the silver-containing catalyst by one or more impregnation methods.
[0064] The alkali metal, alkaline earth metal, rhenium promoter and rhenium co-promoter added in the preparation process of the silver catalyst of the present invention can be deposited on the carrier before, simultaneously or after the silver is impregnated, or can be deposited on the carrier after the silver compound is activated and reduced.
[0065] The fourth aspect of the present invention provides a method for producing an epoxy compound by epoxidation of an olefin, the method comprising: epoxidation of the olefin in the presence of the above-mentioned silver catalyst to obtain the epoxy compound;
[0066] The olefin is preferably at least one selected from styrene, propylene, ethylene and 1,3-butadiene.
[0067] A fifth aspect of the present invention provides use of the epoxy compound produced by the above method as a raw material for producing at least one of ethylene glycol, ethylene glycol ether and ethanolamine.
[0068] In the present invention, the epoxy compound is preferably ethylene oxide.
[0069] The present invention will be further described below in conjunction with embodiments, but the scope of the present invention is not limited to these embodiments.
[0070] Determination of the catalytic performance of the silver catalyst in the following examples and comparative examples:
[0071] The selectivity of various silver catalysts of the present invention was tested using a laboratory microreactor evaluation device. The reactor used in the microreactor evaluation device was a stainless steel reaction tube with an inner diameter of 4 mm, and the reaction tube was placed in a heating jacket. The catalyst was loaded with an inert filler at the bottom so that the catalyst bed was located in the constant temperature zone of the heating jacket.
[0072] The activity and selectivity test conditions used in the present invention are shown in Table 1:
[0073] Table 1
[0074]
[0075] When the above reaction conditions are stably reached, the gas composition at the reactor inlet and outlet is continuously measured. The selectivity is calculated according to the following formula after volume shrinkage correction is performed on the measured results:
[0076] Selectivity
[0077] Wherein, ΔEO is the difference in ethylene oxide concentration between the reactor outlet gas and the inlet gas, ΔCO2 is the difference in carbon dioxide concentration between the reactor outlet gas and the inlet gas, and the average of more than 10 groups of test data is taken as the test result of the day.
[0078] The porosity, tortuosity and pore volume of the α-alumina carriers in the following examples and comparative examples were measured by mercury intrusion porosimetry.
[0079] Example 1
[0080] Weigh 50g of kinematic viscosity is 150mm 2 / s paraffin oil, 200.0g boehmite, 800.0g gibbsite, 40.0g ethyl silicate, 10.5g barium nitrate, 20.0g aluminum fluoride, put into a mixer and mix evenly, transfer to a kneader, add dilute nitric acid (nitric acid: water = 1:3, volume ratio) until kneading into a paste that can be extruded, extrude the paste into a seven-hole cylindrical object, dry at 100°C for more than 24h to reduce the free water content to less than 10%, then put the dried seven-hole cylindrical object into a muffle furnace for roasting, the roasting temperature is 1300°C, the roasting time is 50h, and finally cool to room temperature to obtain an α-alumina carrier. The relevant physical property data of the α-alumina carrier of this embodiment are shown in Table 2.
[0081] Example 2
[0082] Weigh 80g of kinematic viscosity of 250mm 2 / s naphtha, 200.0g boehmite, 600.0g gibbsite, 200.0g α-alumina, 40.0g ethyl silicate, 10.5g barium nitrate, 20.0g aluminum fluoride, put into a mixer and mix evenly, transfer to a kneader, add oxalic acid aqueous solution (oxalic acid: water = 1: 2, mass ratio) until kneading into a paste that can be extruded, press the paste into a sheet, press into a single-hole cylindrical object, dry at 100°C for more than 24h to reduce the free water content to less than 10%, then put the dried single-hole cylindrical object into a muffle furnace for roasting, the roasting temperature is 1240°C, the roasting time is 40h, and finally cool to room temperature to obtain an α-alumina carrier. The relevant physical property data of the α-alumina carrier of this embodiment are shown in Table 2.
[0083] Example 3
[0084] Weigh 250g of kinematic viscosity to 250mm 2 / s of medical white oil, 250.0g of pseudo-monohydrate, 750.0g of θ-alumina, 15.2g of silicon dioxide, 30.4g of calcium carbonate, and 61.0g of ammonium chloride are placed in a mixer and mixed evenly, transferred to a kneader, and dilute nitric acid (nitric acid: water = 1:3, volume ratio) is added until it is kneaded into a paste that can be extruded, and the paste is roll-cut into a single-hole cylindrical object, and dried at 100°C for more than 24h to reduce the free water content to less than 10%, and then the dried single-hole cylindrical object is placed in a microwave oven for roasting, the roasting temperature is 1200°C, the roasting time is 20h, and finally cooled to room temperature to obtain an α-alumina carrier. The relevant physical property data of the α-alumina carrier of this embodiment are shown in Table 2.
[0085] Example 4
[0086] Weigh 100g of kinematic viscosity of 50mm 2 / s industrial white oil, 800.0g pseudo-monohydrate, 100.0g diaspore, 100.0g α-alumina, 30.0g ammonium fluoride, put into a mixer and mix evenly, transfer to a kneader, add dilute nitric acid (nitric acid: water = 1:3, volume ratio) until kneading into a paste that can be extruded, extrude the paste into a four-leaf clover shape, dry at 100°C for more than 24h to reduce the free water content to less than 10%, then put the dried four-leaf clover into a tunnel kiln for roasting, the roasting temperature is 1300°C, the roasting time is 35h, and finally cool to room temperature to obtain an α-alumina carrier. The relevant physical property data of the α-alumina carrier of this embodiment are shown in Table 2.
[0087] Example 5
[0088] Weigh 200g of kinematic viscosity 100mm 2 / s rubber oil, 500.0g boehmite, 200.0g gibbsite, 300.0g α-alumina, 5.0g ethyl silicate, put into a mixer and mix evenly, transfer to a kneader, add dilute nitric acid (nitric acid: water = 1:3, volume ratio) until kneading into a paste that can be extruded, press the paste into a sheet, press into a five-hole cylindrical object, dry at 100°C for more than 24h to reduce the free water content to less than 10%, then put the dried five-hole cylindrical object into a bell kiln for roasting, the roasting temperature is 1400°C, the roasting time is 30h, and finally cool to room temperature to obtain an α-alumina carrier. The relevant physical property data of the α-alumina carrier of this embodiment are shown in Table 2.
[0089] Comparative Example 1
[0090] Weigh 50g of graphite, 200.0g of boehmite, 800.0g of gibbsite, 40.0g of ethyl silicate, 10.5g of barium nitrate, and 20.0g of aluminum fluoride, put them into a mixer and mix them evenly, transfer them into a kneader, add dilute nitric acid (nitric acid: water = 1:3, volume ratio) until kneading into a paste that can be extruded, extrude the paste into a seven-hole cylindrical object, dry it at 100°C for more than 24h to reduce the free water content to less than 10%, then put the dried seven-hole cylindrical object into a muffle furnace for roasting, the roasting temperature is 1300°C, the roasting time is 50h, and finally cool to room temperature to obtain an α-alumina carrier. The relevant physical property data of the α-alumina carrier of this embodiment are shown in Table 2.
[0091] Comparative Example 2
[0092] Weigh 80g petroleum coke, 200.0g boehmite, 600.0g gibbsite, 200.0g α-alumina, 40.0g ethyl silicate, 10.5g barium nitrate, 20.0g aluminum fluoride, put them into a mixer and mix them evenly, transfer them into a kneader, add oxalic acid aqueous solution (oxalic acid: water = 1: 2, mass ratio) until kneading into a paste that can be extruded, press the paste into a sheet, press it into a single-hole cylindrical object, dry it at 60-120°C for more than 24h to reduce the free water content to less than 10%, then put the dried single-hole cylindrical object into a muffle furnace for roasting, the roasting temperature is 1240°C, the roasting time is 40h, and finally cool it to room temperature to obtain an α-alumina carrier. The relevant physical property data of the α-alumina carrier of this embodiment are shown in Table 2.
[0093] Comparative Example 3
[0094] Weigh 100g of kinematic viscosity of 5mm 2 / s industrial white oil, 800.0g pseudo-monohydrate, 100.0g diaspore, 100.0g α-alumina, 30.0g ammonium fluoride, put into a mixer and mix evenly, transfer to a kneader, add dilute nitric acid (nitric acid: water = 1:3, volume ratio) until kneading into a paste that can be extruded, extrude the paste into a four-leaf clover shape, dry at 100°C for more than 24h to reduce the free water content to less than 10%, then put the dried four-leaf clover into a tunnel kiln for roasting, the roasting temperature is 1300°C, the roasting time is 35h, and finally cool to room temperature to obtain an α-alumina carrier. The relevant physical property data of the α-alumina carrier of this embodiment are shown in Table 2.
[0095] Table 2
[0096] Pore volume (ml / g) Porosity (%) Tortuosity Example 1 0.58 60.1 14.7 Example 2 0.61 68.6 12.3 Example 3 0.59 63.7 17.8 Example 4 0.78 70.1 2.3 Example 5 0.60 60.3 9.5 Comparative Example 1 0.56 56.8 28.2 Comparative Example 2 0.57 58.4 25.9 Comparative Example 3 0.56 59.1 23.6
[0097] Example 6
[0098] Add 35.0g of ethylenediamine, 14.0g of ethanolamine, and 40.0g of deionized water to a stirred glass flask to prepare a mixed solution. Slowly add a portion of the prepared silver oxalate paste to the mixed solution, continue stirring to dissolve all the silver oxalate, and the amount of silver oxalate added is such that the prepared impregnation solution contains 24% (weight) of silver. Then add 0.50g of cesium nitrate, 1.0g of barium acetate, and 0.60g of ammonium perrhenate in sequence, and then add deionized water to make the total mass of the solution reach 200g. Mix well to prepare an impregnation solution for standby use. Take 20g of the carrier of Example 1 and put it into a vacuum container, pour in the prepared impregnation solution, immerse the carrier, evacuate to less than 10mmHg, keep for about 30min, and remove the excess solution by leaching. Finally, place the leached carrier in air at 320℃ and heat for 6min, cool it, and prepare a silver catalyst. Among them, the silver oxalate paste is prepared by the following method:
[0099] Weigh 80.0g of silver nitrate and dissolve it in 90.0ml of deionized water, weigh 36.0g of ammonium oxalate and dissolve it in 300.0ml of deionized water, fully dissolve to obtain silver nitrate solution and ammonium oxalate solution, mix the two solutions under vigorous stirring to generate white silver oxalate precipitate. Aging for 1h, filtering, washing the filter cake with deionized water until there is no nitrate ion in the filtrate, and obtaining silver oxalate paste.
[0100] The activity and selectivity of the prepared catalyst were measured using a microreactor evaluation device under the aforementioned process conditions. The test results are listed in Table 3.
[0101] Example 7
[0102] The preparation method of the silver catalyst in Example 6 is the same as that in Example 6 except that 20 g of the carrier in Example 2 is taken.
[0103] The activity and selectivity of the prepared catalyst were measured using a microreactor evaluation device under the aforementioned process conditions. The test results are listed in Table 3.
[0104] Example 8
[0105] Take 20 g of the carrier obtained in Example 3, place the carrier obtained by leaching in air at 350° C. and heat for 3 minutes. The rest is the same as the preparation method of the silver catalyst in Example 6.
[0106] The activity and selectivity of the prepared catalyst were measured using a microreactor evaluation device under the aforementioned process conditions. The test results are listed in Table 3.
[0107] Example 9
[0108] Take 20g of the carrier of Example 4, replace 0.50g of cesium nitrate and 1.0g of barium acetate with 0.50g of cesium sulfate and 1.5g of strontium acetate, and the rest is the same as the preparation method of the silver catalyst in Example 6.
[0109] The activity and selectivity of the prepared catalyst were measured using a microreactor evaluation device under the aforementioned process conditions. The test results are listed in Table 3.
[0110] Example 10
[0111] Take 20 g of the carrier of Example 5, replace 0.60 g of ammonium perrhenate with 0.70 g of ammonium perrhenate, and the rest is the same as the preparation method of the silver catalyst in Example 9.
[0112] The activity and selectivity of the prepared catalyst were measured using a microreactor evaluation device under the aforementioned process conditions. The test results are listed in Table 3.
[0113] Comparative Example 4
[0114] Take 20 g of the carrier of Comparative Example 1, and the rest is the same as the preparation method of the silver catalyst in Example 6.
[0115] The activity and selectivity of the prepared catalyst were measured using a microreactor evaluation device under the aforementioned process conditions. The test results are listed in Table 3.
[0116] Comparative Example 5
[0117] Take 20 g of the carrier of Comparative Example 2, and the rest is the same as the preparation method of the silver catalyst in Example 7.
[0118] The activity and selectivity of the prepared catalyst were measured using a microreactor evaluation device under the aforementioned process conditions. The test results are listed in Table 3.
[0119] Comparative Example 6
[0120] Take 20 g of the carrier of Comparative Example 3, and the rest is the same as the preparation method of the silver catalyst in Example 8.
[0121] The activity and selectivity of the prepared catalyst were measured using a microreactor evaluation device under the aforementioned process conditions. The test results are listed in Table 3.
[0122] Table 3
[0123] Selectivity (%) Reaction temperature (%) Example 6 84.5 217.1 Example 7 84.1 215.8 Example 8 83.8 217.3 Example 9 85.3 212.1 Example 10 85.0 216.8 Comparative Example 4 83.0 224.0 Comparative Example 5 82.5 225.1 Comparative Example 6 83.3 223.4
[0124] By comparing the data in Table 2 and Table 3, it can be seen that the α-alumina prepared by adding organic oily liquid has better pore volume, porosity and lower tortuosity, which shows that this carrier has good pore structure and pore permeability, and the silver catalyst prepared from this carrier also shows good activity and selectivity.
[0125] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. An α-alumina carrier, characterized in that The α-alumina carrier is prepared by a method comprising the following steps: (1) uniformly mixing an organic oily liquid, aluminum hydroxide, optional aluminum oxide, optional silicon-containing compound, optional alkaline earth metal compound and optional mineralizer to obtain a solid mixture; (2) kneading, shaping, drying and calcining the solid mixture and the acid solution to obtain the α-alumina carrier; Wherein, the kinematic viscosity of the organic oily liquid is ≥10mm 2 / s, preferably ≥20mm 2 / s.
2. The α-alumina carrier according to claim 1, wherein The organic oily liquid comprises alkanes and / or aromatic hydrocarbons, preferably at least one of normal alkanes, cycloalkanes and aromatic hydrocarbons, and more preferably at least one of white oil, paraffin oil, rubber oil and naphtha; The white oil is preferably at least one of medical grade white oil, food grade white oil, cosmetic grade white oil and industrial grade white oil.
3. The α-alumina carrier according to claim 1, wherein The aluminum hydroxide includes aluminum oxide monohydrate and optionally aluminum oxide trihydrate; The alumina monohydrate is at least one of boehmite, diaspore and pseudo-alumina monohydrate; The alumina trihydrate is at least one of gibbsite, diaspore and diaspore.
4. The α-alumina carrier according to claim 1, wherein The alumina includes at least one of γ-alumina, θ-alumina, κ-alumina, η-alumina and α-alumina; The silicon-containing compound includes at least one of silicon-containing sol, silicon dioxide, silicic acid, organic silicon and silicate; The alkaline earth metal compound is selected from at least one of the oxides, hydroxides, nitrates, acetates, oxalates and sulfates of alkaline earth metals; the alkaline earth metal is at least one of magnesium, calcium, strontium and barium; The mineralizer is selected from at least one of ammonium fluoride, magnesium fluoride, aluminum fluoride, lithium fluoride, boric acid, zinc fluoride, ammonium chloride and ammonium nitrate.
5. The α-alumina carrier according to claim 1, wherein Based on the total weight of the solid mixture, the amount of the organic oily liquid is 1.0-30.0wt%, the amount of the gibbsite is 15.0-99.0wt%, the amount of the gibbsite is 0-80.0wt%, the amount of the alumina is 0-60.0wt%, the amount of the silicon-containing compound is 0-10.0wt%, the amount of the alkaline earth metal compound is 0-5.0wt%, and the amount of the mineralizer is 0-10.0wt%.
6. The α-alumina carrier according to claim 1, wherein The acid solution includes at least one of a citric acid aqueous solution, a nitric acid aqueous solution, a formic acid aqueous solution, an oxalic acid aqueous solution, an acetic acid aqueous solution, a propionic acid aqueous solution and a hydrochloric acid aqueous solution.
7. The α-alumina carrier according to claim 1, wherein The drying temperature is 60-120°C; The calcination temperature is 1000-1600° C., and the calcination time is 1-70 hours.
8. The α-alumina carrier according to claim 1, wherein The α-alumina carrier has at least one of the following characteristics: porosity ≥45%, preferably ≥60%; tortuosity ≤40, preferably ≤23.
9. The method for preparing an α-alumina carrier according to any one of claims 1 to 8, characterized in that: The preparation method comprises: (1) uniformly mixing the organic oily liquid, aluminum hydroxide, optional aluminum oxide, optional silicon-containing compound, optional alkaline earth metal compound and optional mineralizer to obtain the solid mixture; (2) The solid mixture and the acid solution are kneaded, molded, dried and calcined to obtain the α-alumina carrier.
10. A silver catalyst, characterized in that The silver catalyst is prepared by a preparation method comprising the following steps: firstly, the alumina carrier according to any one of claims 1 to 8 is impregnated with a solution containing an organic amine, a silver-containing compound, an alkali metal additive, an alkaline earth metal additive, an optional rhenium additive and an optional co-additive of the rhenium additive, and then the impregnation solution is leached; and then the carrier obtained by leaching is activated to obtain the silver catalyst.
11. A method for producing epoxy compounds by epoxidation of olefins, characterized in that: The method comprises: carrying out an epoxidation reaction of an olefin in the presence of the silver catalyst as claimed in claim 10 to obtain the epoxide compound; The olefin is preferably at least one selected from styrene, propylene, ethylene and 1,3-butadiene.
12. Use of the epoxy compound produced by the method according to claim 11 as a raw material for producing at least one of ethylene glycol, ethylene glycol ether and ethanolamine.
Citation Information
Patent Citations
Preparation method of catalyst for catalytic decomposition of dioxin generated in nonferrous metal smelting tail gas
CN104549230A
Alpha-alumina carrier used for silver catalyst, preparation method and application of same
CN107413389A
Alpha-alumina carrier, silver catalyst for ethylene epoxidation and ethylene oxidation method
CN109499559A
Alpha-alumina carrier, preparation method thereof, silver catalyst and method for producing ethylene oxide through ethylene epoxidation
CN114100596A